Control of single-phase electrolytic capacitor-less isolated converter for DC low voltage residential networks - Santos, Nelson (2020)
In recent years, there has been a desire to improve electricity generation and consumption, to reach sustainability. Technological solutions today allow a rational use of electricity with good overall performance. Traditionally, from production to distribution, electrical energy is AC-supported for compatibility reasons and easy voltage level transformation. However, nowadays most electric loads need DC power to work properly. A single high-efficiency central AC-DC power converter may be advantageous in eliminating several less efficient AC-DC embedded converters, distributed all over a residential area. This paper presents a new single-phase AC-DC converter using one active bridge (most isolated topologies are based on the dual active bridge concept) and a high-frequency isolation transformer with low-value non-electrolytic capacitors, together with its control system design. The converter can be introduced into future low-voltage DC microgrids for residential buildings, as an alternative to several embedded AC-DC converters. Non-linear control techniques (sliding mode control and the Lyapunov direct method) are employed to guarantee stability in the output DC low voltage with near unity power factor compensation in the AC grid. The designed converter and controllers were simulated using Matlab/Simulink and tested in a lab experimental prototype using digital signal processing (DSP) to evaluate system performance.